2003
DOI: 10.1038/sj.bjp.0705324
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced anti‐inflammatory potency of a nitric oxide‐releasing prednisolone derivative in the rat

Abstract: 1 Derivatization of nonsteroidal anti-inflammatory drugs, such that they release nitric oxide (NO) in small amounts, has been shown to significantly increase their anti-inflammatory activity and analgesic potency. In this study, we compared the anti-inflammatory potency of prednisolone to a nitric oxidereleasing derivative of prednisolone (NCX-1015). 2 Carrageenan-induced inflammation of an airpouch in the rat was used. The rats were pretreated with equimolar doses of prednisolone or NCX-1015 and the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 29 publications
2
26
0
1
Order By: Relevance
“…In the present study, we demonstrated that the anti-inflammatory potency of flunisolide could be markedly increased (ϳ40-fold) by addition, through an ester linkage, of a NO-releasing moiety. This increase in potency is consistent with previous studies in which NOreleasing derivatives of prednisolone have been examined in experimental inflammation models (Paul-Clark et al, 2000Fiorucci et al, 2002a;Turesin et al, 2003). NCX-1024 was found to be more active in suppressing endotoxin-induced up-regulation of COX-2 mRNA expression and NF-B activation, which may contribute to the observed increase in anti-inflammatory potency.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…In the present study, we demonstrated that the anti-inflammatory potency of flunisolide could be markedly increased (ϳ40-fold) by addition, through an ester linkage, of a NO-releasing moiety. This increase in potency is consistent with previous studies in which NOreleasing derivatives of prednisolone have been examined in experimental inflammation models (Paul-Clark et al, 2000Fiorucci et al, 2002a;Turesin et al, 2003). NCX-1024 was found to be more active in suppressing endotoxin-induced up-regulation of COX-2 mRNA expression and NF-B activation, which may contribute to the observed increase in anti-inflammatory potency.…”
Section: Discussionsupporting
confidence: 78%
“…They further showed that a similar derivatization of prednisolone, but without the NO-releasing (ONO 2 ) group, did not affect antiinflammatory potency. Turesin et al (2003) demonstrated that coadministration of prednisolone with a DETA-NONOate, an NO donor, resulted in a significantly greater reduction of leukocyte infiltration and inflammatory mediator production in a rat airpouch model than was observed with either drug alone. NO can exert many anti-inflammatory effects, including reduction of leukocyte adherence to the vascular endothelium (Gauthier et al, 1994) and suppression of production of various chemotactic factors (Walford and Loscalzo, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The samples were reconstituted in 200 l of phosphate-buffered saline (pH 7.4) and stored at Ϫ70°C until measurement of PGE 2 content by ELISA was performed (Wallace et al, 2000). In some experiments, the right hemisphere of the brain from each rat was excised and processed for detection of COX-1 and COX-2 expression by Western blotting, as described in detail previously (Turesin et al, 2003).…”
Section: Methodsmentioning
confidence: 99%